2009
DOI: 10.1089/apc.2008.0175
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity and Remission of Fatigue in Patients with Established HIV Infection

Abstract: Fatigue is one of the most common and debilitating complaints of HIV-positive individuals, potentially leading to important functional limitations. We recruited 128 HIV-positive individuals (fatigued and nonfatigued) between March 2005 and May 2006; 66% were male, 66% were African American, 45% had greater than a high school education, 67% were unemployed, and ages ranged from 26-66 (median, 44). Every 3 months for 15 months, participants completed a 56-item self-report fatigue scale developed and validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
3
21
1
Order By: Relevance
“…Thus, these variables were not retained as covariates. These findings contradict prior reports of associations between fatigue and age (Bower et al, 2013), ART (Jong et al, 2010; Pence et al, 2009), and BMI (Bower et al, 2013). In addition to the potentially confounding influence of race/ethnicity and gender, other possible explanations for the divergent findings may pertain either to the way in which fatigue is measured or to the heterogeneity in study designs and sample characteristics across studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Thus, these variables were not retained as covariates. These findings contradict prior reports of associations between fatigue and age (Bower et al, 2013), ART (Jong et al, 2010; Pence et al, 2009), and BMI (Bower et al, 2013). In addition to the potentially confounding influence of race/ethnicity and gender, other possible explanations for the divergent findings may pertain either to the way in which fatigue is measured or to the heterogeneity in study designs and sample characteristics across studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Although much of the research on inflammation, cytokines and fatigue focuses on adults with cancer, fatigue is a well-documented symptom among adults living with HIV, with an estimated 33%–88% of adults with HIV/AIDS experiencing fatigue (Barroso and Voss, 2013; daCosta DiBonaventura et al, 2012; Jong et al, 2010; Lee et al, 2009; Millikin et al, 2003; Pence et al, 2009; Sullivan and Dworkin, 2003). Fatigue was associated with some of the early immunotherapies for HIV/AIDS, such as interferon alpha (Finter et al, 1991) and IL2 (Grady et al, 1998) but otherwise, the relationship between inflammatory markers and fatigue in adults living with HIV is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue has also been reported to be a very common symptom among HIV-positive individuals, which has been associated with functional limitations, higher mortality, and unemployment. 55,56 The relationship between several of these correlates (such as depression, use of substances, and unemployment) and QOS was also observed in our study. Conversely, among other correlates of quality of sleep, there are conflicting reports regarding the relationship between QOS and CD4 + cell count or HIV viral load.…”
Section: Discussionsupporting
confidence: 79%
“…Further, 55–65% of people living with HIV (PLWH) commonly report fatigue after initiating antiretroviral therapy (ART; Henderson, Safa, Easterbrook, & Hotopf, 2005; Pence et al, 2009; Voss, 2005). Negative outcomes of HIV-related fatigue (HRF) include reduced quality of life, social isolation, depression and anxiety, sleep disturbances, weakness, muscle aches, lack of concentration, and impaired memory function (Voss, 2005).…”
mentioning
confidence: 99%
“…Yet, multiple investigators have recognized the subjectivity of using this type of measure for fatigue, with one patient describing mild fatigue as a state that another may describe as severe (Pence et al, 2009; Rodriguez, 2000). Pence and colleagues further demonstrated that self-reported severity of fatigue is very resistant to change over a period of 15 months.…”
mentioning
confidence: 99%